Formation of rational range for running repairs of front-end shovel loader gearbox - Acel Zhandarbekova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The work relevancy is caused by the necessity to sustain the required reliability level of road-building machines operating in real hard conditions at optimum level of costs on running repair of aggregates. The work goal is to justify the formation of rational range of aggregates running repair. These aggregates belong to series-produced road-building machines by computer modeling of their reliability when machine purchase and operation costs are taken into account. Research methods: while carrying out the researches the author has used the up-to-date methods providing reliability of engineering systems, the theory of maintainable item efficiency restoration and computer modeling. The method for reducing costs on maintenance of machine aggregates in real operation conditions was chosen as the increasing reliability of parts and units which limit their reliability. The results. The author proposed the enhanced modeling sequence of reliability level of machines aggregates consisting of six stages. This sequence was tested on gearbox SB165-2 of front-end shovel loaders L-34B and 534C. The mathematical model of computer calculation program was developed to evaluate the influence of machines parts and units production quality on output factors of concerned aggregate reliability and to achieve the work goal practically. The goal is to form rational range of machine aggregate running repairs. It was proved that while using optimal running repairs of gearbox SB 165-2 of front-end shovel loaders it is possible to reduce minimum total cost per unit Cspecmin on reliability maintenance of the aggregate under concern to 15,1 %.